PENERAPAN SISTEM PENGENDALIAN BERBASIS SPIRITUALITAS PADA HOTEL MM, BELILAS. - Lyvia Wilgo Lensia; Sujoko Efferin (Perpustakaan Universitas Surabaya, 2018)
This study is applied research with the purpose of explanatory reasearh to solve the problems that occurred in MM Hotel, Riau which will produce recommendations in the form of solving and solving the problem by using interpretive-qualitatvie research paradigma. This research is an opportunity to put the spirituality in MM Hotel and surrounding area. In Indonesia, especially in remote parts of Riau, the concept of spirituality-based management control system is not known by many people. By implementing a spirituality based management control system, it is expected to reduce the suffering around us and create a better world for all beings and a harmonious and loving world.